Faouda Wa Ruina: A History of Moroccan Punk Rock and Heavy Metal - (:unkn) unknown (My University, 2018)
ABSTRACT FAOUDA WA RUINA: A HISTORY OF MOROCCAN PUNK ROCK AND HEAVY METAL by Brian Trott The University of Wisconsin-Milwaukee, 2018 Under the Supervision of Professor Gregory Carter While the punk rock and heavy metal subcultures have spread through much of the world since the 1980s, a heavy metal scene did not take shape in Morocco until the mid-1990s. There had yet to be a punk rock band there until the mid-2000s. In the following paper, I detail the rise of heavy metal in Morocco. Beginning with the early metal scene, I trace through critical moments in its growth, building up to the origins of the Moroccan punk scene and the state of those subcultures in recent years. I also discuss in depth the organization of concerts and music festivals in Morocco. I argue that Moroccan youth creatively engage with globalized media, to create original, subjective interpretations of said media. This paper is split into sections of analysis and sections of narrative based on interviews I conducted with members of the Moroccan punk and metal scenes.
Keywords: Heavy Metal; Moroccan; Morocco; North Africa; Punk Rock; Subculture